Eksplorasi Potensi Penggunaan Blockchain Dalam Optimalisasi Manajemen Pelabuhan di Indonesia: Tinjauan Literatur - Nicholas Dwinovan; Arif Rachman Dillah; Fakhri Najmuddin; Kencana Verawati (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research explores the potential use of Blockchain technology to optimize port management in Indonesia, which is a crucial element in the global supply chain. The research method employed is a literature review, with analysis and synthesis of information to understand Blockchain's contribution to improving port management. The identified potential uses of Blockchain include real-time logistics tracking and monitoring, data validation and authentication, increased transparency and trust, and port process efficiency. The study also highlights the use of smart technology and smart contracts in port management, as well as challenges in adopting Blockchain technology. A comprehensive conceptual framework is proposed for the application of Blockchain in Indonesia's maritime industry, including a feasibility analysis framework to assess implementation readiness. The results of this literature review are expected to provide deep insights and serve as a foundation for further research and assist stakeholders in making decisions related to the application of Blockchain technology in port management.